Współczesne tendencje w badaniach nad nauczycielem. Na przykładzie lematów badawczych prezentowanych na wybranych konferencjach naukowych organizowanych przez dwa światowe stowarzyszenia edukacyjne - Dylak, Stanisław; Wawrzyniak, Krzysztof (Wydawnictwo Naukowe UAM w Poznaniu, 2003)
In this article, the authors - using conferences’ proceedings - try to define the contemporary directions in research on teacher and teacher education i.e. in the study on teacher. The Authors took into consideration over 1200 papers presented on five international conferences organized by two world wide known educational organizations: ISATT - International Study Association for Teacher and Teaching and AECT - Association of Communication and Educational Technology. They were looking for presentations analyzing research results on teacher and teacher education. The Authors tried to categorize that research subjects. Eight main directions have been defined: Teacher's work - strategies, competences; teacher education; becoming a teacher - building the knowledge; teacher professional development and improvement; teachers learning in a workplace; context, environment and conditions for teacher's working; teachers thinking about themselves and the thinking about teachers; investigative approaches in a study on teachers.
Contemporary directions in the research on teacher and teacher education. On the base of papers presented on several international conferences organized by two worldwide educational associations